2012
DOI: 10.2220/biomedres.33.63
|View full text |Cite
|
Sign up to set email alerts
|

Difference in glucose intolerance between C57BL/6J and ICR strain mice with streptozotocin/nicotinamide-induced diabetes

Abstract: Blood glucose and plasma insulin levels between C57BL/6J and ICR strain mice with nicotinamide (NA) and streptozotocin (STZ)-induced diabetes were compared to establish a suitable strain of the experimental diabetic mouse model. The mice were intraperitoneally treated twice with STZ (100 mg/kg) 15 min after injection of NA (120 mg/kg) at a 1-day interval, and non-fasting blood glucose level was then weekly monitored for 5 weeks. The blood glucose level in ICR mice gradually increased and was about 2-times high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 15 publications
2
23
0
Order By: Relevance
“…3 was collected from ICR mice. ICR mice are w5 g heavier than equivalent agematched C57BL/6 mice, and there are established differences in glucose metabolism between the two strains, particularly in models of diabetes (Luo et al 1998, Burgess et al 2005, Shimizu et al 2012. Thus this is most likely due to variations in glucose metabolism between different mouse strains as mentioned previously (Andrikopoulos et al 2008, Berglund et al 2008, and reinforces the point that rodent strain is an important factor to be taken into consideration when comparing between studies.…”
Section: Route and Dose Of Glucose Administrationmentioning
confidence: 58%
“…3 was collected from ICR mice. ICR mice are w5 g heavier than equivalent agematched C57BL/6 mice, and there are established differences in glucose metabolism between the two strains, particularly in models of diabetes (Luo et al 1998, Burgess et al 2005, Shimizu et al 2012. Thus this is most likely due to variations in glucose metabolism between different mouse strains as mentioned previously (Andrikopoulos et al 2008, Berglund et al 2008, and reinforces the point that rodent strain is an important factor to be taken into consideration when comparing between studies.…”
Section: Route and Dose Of Glucose Administrationmentioning
confidence: 58%
“…The toxin causes a reduction in insulin production and subsequent hyperglycemia with the severity depending on the strain of the rodent (Rodrigues et al, 1997, Shimizu et al, 2012) and the dose of STZ (Ventura-Sobrevilla et al, 2011). Typically induced between 11-week to 14-week of age in either mice or rats, STZ-T1D impedes normal bone mass accrual resulting in lower structural strength of cortical bone and reduced trabecular bone within several weeks as compared to non-diabetic controls (Nyman et al, 2011, Silva et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…30) The ICR mouse strain with experimental diabetes induced by NA/STZ-treatment is more sensitive to hyperglycemia under diabetic conditions than the C57BL/6J strain. 17) Using the NA/STZ-induced diabetic mouse model, the objective was to elucidate the protective effects of supplementary SeMet on oxidative stress in pancreatic islets under insufficient and physiological Se levels because this selenocompound improves pancreatic GPX1 activity the most in mice with insufficient dietary Se status.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we demonstrated that the ICR mouse strain mildly induced by nicotinamide (NA) and streptozotocin (STZ) was an appropriate model of diabetes. 17) There are conflicting reports on the relevance between supplementary Se or the physiological status and the prevalence of type 2 diabetes. Previous studies demonstrate that Se status of diabetic patients are physiologically insufficient compared with healthy individuals.…”
mentioning
confidence: 99%